Report of the Workshop on Eel and CITES (WKEELCITES) - ICES (11907872) (2015)
The Workshop on Eel and CITES met at the ICES Headquarters, Copenhagen from 10th to 12th March 2015, under the chairmanship of Alan Walker (UK). The Workshop was attended by seven experts in eel assessment and management, two experts in CITES, plus observers from eel industry and CITES Scientific Authorities, and one independent reviewer. A second reviewer participated by correspondence. The European Eel (Anguilla anguilla) is listed in CITES Appendix II and in Annex B to Council Regulation (EC) No 338/97 since 13 March 2009. Since that date, the CITES Scientific Review Group (SRG) has been monitoring whether a “Non-Detriment Find-ing” (NDF) could be made for the species, i.e. whether exports from and imports into the EU would have a harmful effect on the conservation status of the species. This has been done on the basis of SRG guidelines (http://ec.europa.eu/environ-ment/cites/pdf/srg/guidelines.pdf). In December 2010, the SRG came to the conclusion that the situation of the stock was too critical to be able to find that international trade could be permitted without detriment to the survival of the species. Exports from and imports into the EU of Anguilla anguilla have therefore been suspended since that date. In that context, ICES is requested to provide scientific information and advice on the following issues: What criteria (and if possible, what thresholds) that a Non-Detriment Finding in the future. An assessment of the scale that could be used to make a Non-Detriment Finding. An assessment of possible conditions that could be used in association with could be used to make a Non-Detriment Finding (e.g. quota, or size of specimens, or any other condition).